Modeling Singular Value Decomposition and K-Means of Core Image in Clasification of Potential Nickel - Agung Prajuhana Putra; Agus Buono; Bib Paruhum Silalahi (Institute of Advanced Engineering and Science, 2015)
Exploration is a main process in the nickel mining activities. One of the most important steps in exploration is obtain soil samples (cores) to determine the potential of nickel in the soil. Laboratory testing is a way to know how much the nickel content on the core. This research aims to utilize the core image of the statistical characteristics of color and texture, Biplot analysis using SVD, K-Means and identification using SVM method with RBF kernel and polynomial to determine the potential of nickel.DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7197